The Effect of University Fees on Applications, Attendance and Course Choice: Evidence from a Natural Experiment in the UK. (21st July 2018) - Sá, Filipa
Abstract : Over the past two decades, large changes have been introduced to the level of university fees in the UK, with significant variation across countries. This paper exploits this variation to examine the effect of fees on university applications, attendance and course choice. It finds that applications decrease in response to higher fees with an elasticity of demand of about −0.4. Attendance also decreases. The reduction in applications and attendance is larger for courses with lower salaries and employment rates after graduation, for non‐STEM subjects, and for less selective universities.